Основні концепції і нові підходи до вирішення проблем професійної освіти : методичні вказівки до виконання контрольної роботи з дисципліни для здобувачів вищої освіти денної та заочної форм навчання другого (магістерського) рівня інженерних та інженерно-педагогічних спеціальностей [Електронний ресурс] - Мальована, Вікторія Володимирівна; Антонова, Алевтина Михайлівна; Malovana, Victoria Volodymyrivna; Antonova, Alevtyna Mikhailovna (Харків : Харківський національний університет імені В. Н. Каразіна, 2025)
Метою вивчення навчальної дисципліни є формування у здобувачів цілісного уявлення щодо історичного контексту розвитку професійної сфери та новітніх досягнень з основних концепцій сталого розвитку суспільства, освіти і методології наукового пізнання у сфері професійної освіти; досвіду створення освітнього середовища професійної освіти, що є сприятливим для здобувачів освіти і забезпечує досягнення визначених результатів навчання.

The purpose of studying the academic discipline is to form in the students a holistic understanding of the historical context of the development of the professional sphere and the latest achievements in the basic concepts of sustainable development of society, education and methodology of scientific knowledge in the field of professional education; experience in creating an educational environment of professional education that is favorable for students and ensures the achievement of certain learning outcomes.
Basic concepts and new approaches to solving problems of professional education : methodological instructions for performing control work on the discipline for applicants of full-time and part-time forms of study of the second (master's) level of higher education of engineering and engineering-pedagogical specialties [Electronic resource]
В авторській редакції
Keywords: SOCIAL SCIENCES::Social sciences::Education::Subject didactics; SOCIAL SCIENCES::Social sciences::Pedgogical work; HUMANITIES and RELIGION::History and philosophy subjects::Philosophy subjects; філософія освіти; культурний досвід; еволюція освіти; християнська філософія; євроінтеграція; philosophy of education; cultural experience; evolution of education; christian philosophy; european integration